2012
DOI: 10.1093/ntr/nts101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varenicline on Abstinence and Smoking Reward Following a Programmed Lapse

Abstract: Introduction: Varenicline (Chantix®) is an effi cacious fi rstline medication for smoking cessation. Studies suggest that one mechanism by which varenicline facilitates sustained smoking abstinence is by reducing the likelihood of relapse to smoking when a lapse, or slip, occurs during a quit attempt. The present study extends this line of research by conducting a prospective laboratory study to examine the relapse prevention effects of varenicline following a programmed lapse. Methods:Daily smokers ( N = 47) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 45 publications
6
57
2
1
Order By: Relevance
“…Finally, we also found that demand reduction by oxytocin predicted attenuation of relapse behavior, supporting the value of demand as an addiction biomarker. This observation is consistent with a recent human study (47) that found a pharmacotherapy that reduced demand for cigarettes also increased the duration patients remained abstinent. Finally, although oxytocin is a peptide and therefore may not cross the blood-brain barrier, systemic administration nevertheless produces robust central activation of oxytocin neurons in supraoptic and paraventricular nuclei (48), indicating systemic oxytocin administration is a viable method of inducing central nervous system (CNS) release of oxytocin and altering CNS activity.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we also found that demand reduction by oxytocin predicted attenuation of relapse behavior, supporting the value of demand as an addiction biomarker. This observation is consistent with a recent human study (47) that found a pharmacotherapy that reduced demand for cigarettes also increased the duration patients remained abstinent. Finally, although oxytocin is a peptide and therefore may not cross the blood-brain barrier, systemic administration nevertheless produces robust central activation of oxytocin neurons in supraoptic and paraventricular nuclei (48), indicating systemic oxytocin administration is a viable method of inducing central nervous system (CNS) release of oxytocin and altering CNS activity.…”
Section: Discussionsupporting
confidence: 93%
“…These results are interpreted cautiously since efficacy was not the purpose of this study, but are not surprising given previous studies that have shown similar results with VAR and NAC as monotherapies (4-6, 8-10, 17, 26). Given that participants had varying readiness to quit motivation and were provided with only minimal encouragement to quit smoking during the study, it is not unexpected that we failed to identify continuous abstinence.…”
Section: Discussionsupporting
confidence: 75%
“…VAR appears to promote abstinence through decreasing withdrawal symptoms and blunting the reward derived from smoking (7). Smokers treated with VAR compared to placebo reported cigarette smoking to be less satisfying and rewarding (8-10). The most common adverse events reported with VAR include nausea, insomnia, abnormal dreams and headache (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…In a wide diversity of populations, higher levels of tobacco demand are consistently associated with greater nicotine dependence (Chase et al 2013, Few et al 2012, Liao et al 2013, MacKillop & Tidey 2011, MacKillop et al 2008, Murphy et al 2011). Also consistent with a role for drug demand in substance dependence, compared with smokers receiving a placebo, those who were administered the efficacious smoking-cessation medication varenicline showed significant increases in demand elasticity for cigarettes (McClure et al 2013). …”
Section: Processes Engendering Reinforcer Pathologymentioning
confidence: 71%